Closed-loop augmented reality towards accurate human-robot collaboration. Issue 1 (2020) - Wang, Xi Vincent; Wang, Lihui; Lei, Mingtian; Zhao, Yongqing
Abstract: Augmented Reality provides an interactive approach to combining the physical manufacturing environment with the computer-generated virtuality. However, it is still challenging to establish an efficient AR system due to the complexity of the actual manufacturing environment, and difficulties in human-robot collaboration. In this research, a feasible AR system is developed with a novel closed-loop structure. A feasible AR-based human-robot interaction method is also developed based on the HoloLens device, together with an advanced compensation mechanism towards accurate robot control. The proposed work is implemented and validated through case studies, and quantifiable performance assessment on system response time, compensation accuracy, etc.